Two’S Not Always Company: Collaborative Information Seeking Across Task Types - Gonzalez-Ibanez, R (Emerald Group Publishing Ltd., 2017)
Purpose: The purpose of this paper is to investigate when and how people working collaboratively could be assisted in a fact-finding task, specifically focusing on team size and its effect on the outcomes of such a task. This is a follow-up to a previously published study that examined exploratory search tasks. Design/methodology/approach: This research investigates the effects of team size on fact-finding tasks using a lab study involving 68 participants – 12 individuals, ten dyads, and 12 triads. The evaluation framework developed in the preceding work is used to compare the findings with respect to the earlier traditional exploratory task (Task 1) and the complex fact-finding task reported here (Task 2), with task type being the only difference. Findings: The analyses of the user study data show that while adding more people to an exploratory search task could be beneficial in terms of efficiency and effectiveness, such findings do not apply in a complex fact-finding task. Indeed, results showed that the individuals were more efficient and effective doing Task 2 than they were in Task 1. Moreover, they outperformed the dyads and triads in Task 2 with respect to these two measures, which relate to the coverage of useful information and its relation to the expression of information needs. If the total time taken by each team is disregarded, the dyads and triads did better than the individuals in answering the fact-finding questions. But considering the time effect, this performance boost does not keep up with the increased group size. Originality/value: The findings shed light not only on when, how, and why certain collaborations become successful, but also how team size affects specific aspects of information seeking, including information exposure, information relevancy, information search, and performance. This has implications for system designers, information managers, and educators. The presented work is novel in that it is the first empirical work to show the difference in individual and collaborative work (by dyads and triads) between exploratory and fact-finding tasks. © 2017, © Emerald Publishing Limited.
Keywords: Evaluation; Tasks; Group work; Information seeking; Collaborative search; Fact-finding